TRAINING AND MENTORING IN PREPARING FINANCIAL STATEMENTS AT BUMDES MERTA SARI - Nur Khamisah; Yusnaini Yusnaini; Asfeni Nurullah; Nilam Kesuma; Muhammad Hidayat; Abdul Rohman (COMMENT: Journal of Community Empowerment, 2022)
BUMDes is a form of village institution which has activities to carry out economic activities or business to obtain useful benefits for the welfare of the community. The existence of BUMDes is expected to improve the living standards of the surrounding village communities. For that, it is necessary to carry out a good management in its financial management. Meanwhile, the majority of BUMDes BUMDes Merta Sari managements are still not very familiar with Accounting and Financial Statements. Therefore, this activity to the community is carried out with the aim of providing training and mentoring to the BUMDes Merta Sari managements in Banyu Urip Village. After the activity is completed, the managements of the BUMDes Merta Sari’s business unit in Banyu Urip Village have the ability to preparing financial Statements as a form of accountability to members who had invested in the business unit of the BUMDes Merta Sari, and to the managements of Banyu Urip Village.Keywords: BUMDES, Accounting, Financial statement